Epidemiology, Clinical Features, and Antimicrobial Resistance of Invasive Escherichia Coli Disease in Patients Admitted in Tertiary Care Hospitals. (27th January 2023) - Doua, Joachim; Geurtsen, Jeroen; Rodriguez-Baño, Jesus; Cornely, Oliver A; Go, Oscar; Gomila-Grange, Aina; Kirby, Andrew; Hermans, Peter; Gori, Andrea; Zuccaro, Valentina; Gravenstein, Stefan; Bonten, Marc; et al.
Abstract: Background: Invasive Escherichia coli disease (IED), including bloodstream infection, sepsis, and septic shock, can lead to high hospitalization and mortality rates. This multinational study describes the clinical profile of patients with IED in tertiary care hospitals. Methods: We applied clinical criteria of systemic inflammatory response syndrome (SIRS), sepsis, or septic shock to patients hospitalized with culture-confirmed E coli from urine or a presumed sterile site. We assessed a proposed clinical case definition against physician diagnoses. Results: Most patients with IED (N = 902) were adults aged ≥60 years (76.5%); 51.9%, 25.1%, and 23.0% of cases were community-acquired (CA), hospital-acquired (HA), and healthcare-associated (HCA), respectively. The urinary tract was the most common source of infection (52.3%). Systemic inflammatory response syndrome, sepsis, and septic shock were identified in 77.4%, 65.3%, and 14.1% of patients, respectively. Patients >60 years were more likely to exhibit organ dysfunction than those ≤60 years; this trend was not observed for SIRS. The case-fatality rate (CFR) was 20.0% (60–75 years, 21.5%; ≥75 years, 22.2%), with an increase across IED acquisition settings (HA, 28.3%; HCA, 21.7%; CA, 15.2%). Noticeably, 77.8% of patients initiated antibiotic use on the day of culture sample collection. A total of 65.6% and 40.8% of E coli isolates were resistant to ≥1 agent in ≥1 or ≥2 drug class(es). A 96.1% agreement was seen between the proposed clinical case definition and physician's diagnoses of IED. Conclusions: This study contributes valuable, real-world data about IED severity. An accepted case definition could promote timely and accurate diagnosis of IED and inform the development of novel preventative strategies. Abstract : IED is associated with prolonged hospitalization, extensive medical resource use, and mortality. Many patients develop SIRS, sepsis, and septic shock. The main source of infection is the urinary tract. An IED clinical case definition could promote timely and accurate diagnosis.